Analisis Kualitatif Standar Kelayakan Perekonomian Pedagang Kaki Lima di Kota Cilegon - Putra, Arta Rusidarma; Aribowo, Aribowo (Yayasan Pondok Pesantren Sunan Bonang Tuban, 2024)
Street vendors are a number of people who carry out trading activities both production and sale of goods or services in strategic and crowded places in urban areas with relatively small capital capabilities and try to make ends meet. The study aims to determine how the existence of street vendors as an informal sector, how much the contribution of household income and the benefits received by traders to the fulfillment of Decent Living Needs. The method used is descriptive qualitative through interviews guided by a list of questions to 50 traders as a sample along Kyai Wasyid Street and Kranggot Market Street Cilegon. The results showed that 52% of traders sell on the sidewalk, 20% on the road, 22% in the parking lot or shopfront, 6% in the yard. Merchandise in the form of ready-to-eat cooked food 42%, unprocessed food 24%, non-food products 26%, and 8% services. The income received by traders each month is linked to the Decent Living Needs which 66% of traders have met, 34% have not met due to the number of family dependents, between four and five people. Of the 20 pedestrian and motor vehicle respondents on the pedestrian path, 35% stated that they were disturbed, 45% were not disturbed and 20% were slightly disturbed by the activities of traders. Thus, it is necessary to control and direct street vendors by the City Planning Office so that they do not use roads and sidewalks for selling, provide parking facilities and trash bins and area solutions for street vendors to maintain the beauty and comfort of Cilegon City